2009
DOI: 10.3844/ajidsp.2009.135.141
|View full text |Cite
|
Sign up to set email alerts
|

The Flavonoid, Quercetin, Inhibits HIV-1 Infection in Normal Peripheral Blood Mononuclear Cells

Abstract: Problem statement: Flavonoids and related polyphenols, have been known to possess cardioprotective, anti-tumor, anti-inflammatory, anti-allergic and anti-viral activities. Previous studies have shown that flavonoid, quercetin significantly downregulates expression of pro-inflammatory cytokines in cultured cells via modulation of NFκB and p38MAPK signaling pathways. In the current study, we hypothesize that quercetin exerts anti-HIV activity by differential modulation of pro-and anti-inflammatory cytokine expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…30 Polyphenols have been associated to prevention of degenerative diseases in human and this was mainly attributed to their antioxidant properties. 31 Among the phenolics, anthocyanin and flavonol contents were further determined in acerola juice. The major anthocyanins identified in acerola varieties were cyanidin-3-rhamnoside and pelargonidin-3-rhamnoside.…”
Section: Discussionmentioning
confidence: 99%
“…30 Polyphenols have been associated to prevention of degenerative diseases in human and this was mainly attributed to their antioxidant properties. 31 Among the phenolics, anthocyanin and flavonol contents were further determined in acerola juice. The major anthocyanins identified in acerola varieties were cyanidin-3-rhamnoside and pelargonidin-3-rhamnoside.…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids (quercetin) was reported to exhibit both anti-infective and antireplicative HIV abilities. Quercetin significantly downregulates p24 antigen production, LTR gene expression and viral infectivity in a dose-dependent manner (5-50 mM) and further downregulation of the expression of the pro-inflammatory cytokine TNF-α with concomitant upregulation of anti-inflammatory cytokine IL-13 [93]. A higher level of IL-13 is known to inhibit TNF-α production and also HIV-1 infection.…”
Section: Flavonoidsmentioning
confidence: 99%
“…107 Researchers have concluded that quercetin's antiviral activity is a result of a variety of multiple actions. Some of the primary mechanisms may include one or more of the following: (1) reducing the ability of a virus to infect cells (infectability), 108 (2) inhibiting the ability of infected cells to replicate and reproduce, 108 and (3) reducing resistance of infected cells to pharmaceutical drug therapy. 109 It is reported that within each of these categories, quercetin has demonstrated (in vivo) chemical interactions of multiple cellular pathways that inhibit or promote the production of critical viral proteins.…”
Section: Enkhtaivan Et Al Reported a Strong Correlation Between Antiomentioning
confidence: 99%